Key Guidelines for Responding to Reviewers [version 2; peer review: 2 approved, 1 approved with reservations] - Sana Salah; Hela Kamoun; Saida Hidouri; Anis Jellad; Helmi Ben Saad (F1000Research, 2024)
Background The process of preparing a scientific manuscript is intricate, encompassing several critical stages, including pre-writing, research development, drafting, peer review, editing, publication, dissemination, and access. Among these, the peer review process (PRP) stands out as a pivotal component requiring seamless collaboration among editors, reviewers, and authors. Reviewers play a crucial role in assessing the manuscript’s quality and providing constructive feedback, which authors must adeptly navigate to enhance their work and meet journal standards. This process can often appear daunting and time-consuming, as authors are required to address numerous comments and requested changes. Authors are encouraged to perceive reviewers as consultants rather than adversaries, viewing their critiques as opportunities for improvement rather than personal attacks. Methods Opinion article. Aim To equip authors with practical strategies for engaging effectively in the PRP and improving their publication acceptance rates. Results Key guidelines include thoroughly understanding and prioritizing feedback, maintaining professionalism, and systematically addressing each comment. In cases of significant disagreement or misunderstanding, authors have the option to refer the issue to the editor. Crafting a well-organized and scientific “response to reviews” along with the revised manuscript can substantially increase the likelihood of acceptance. Best practices for writing an effective response to reviews include expressing gratitude, addressing major revisions first, seeking opinions from co-authors and colleagues, and adhering strictly to journal guidelines. Emphasizing the importance of planning responses, highlighting changes in the revised manuscript, and conducting a final review ensures all corrections are properly documented. Conclusion By following these guidelines, authors can enhance their manuscripts’ quality, foster positive relationships with reviewers, and ultimately contribute to scholarly advancement.